Relationships between wild bees, hoverflies and pollination success in apple orchards with different landscape contexts. (25th September 2015) - Földesi, Rita; Kovács‐Hostyánszki, Anikó; Kőrösi, Ádám; Somay, László; Elek, Zoltán; Markó, Viktor; Sárospataki, Miklós; Bakos, Réka; Varga, Ákos; Nyisztor, Katinka; Báldi, András
Abstract: Pollination is an important ecosystem service because many agricultural crops such as fruit trees are pollinated by insects. Agricultural intensification, however, is one of the main drivers resulting in a serious decline of pollinator populations worldwide. In the present study, pollinator communities were examined in 12 apple orchards surrounded by either homogeneous or heterogeneous landscape in Hungary. Pollinators (honey bees, wild bees, hoverflies) were surveyed in the flowering period of apple trees. Landscape heterogeneity was characterized within a radius of 300, 500 and 1000 m around each orchard using Shannon's diversity and Shannon's evenness indices. We found that pollination success of apple was significantly related to the species richness of wild bees, regardless the dominance of honey bees. Diversity of the surrounding landscape matrix had a marginal positive effect on the species richness of hoverflies within a radius of 300 m and a positive effect on the species richness of wild bees within a radius of 500 m, whereas evenness of the surrounding landscape enhanced the abundance of wild bees within a radius of 500 m. Flower resources in the groundcover within the orchards supported honey bees. Therefore, the maintenance of semi‐natural habitats within 500 m around apple orchards is highly recommended to enhance wild pollinator communities and apple production.